Adsorption characteristics of doped MIL-101(Cr) and CO2 system - Goh, Jia Lin (2017)
To date, reducing carbon dioxide (CO2) emissions and lowering the level of greenhouse gases in our atmosphere have become rising environmental concerns. To increase our environmental sustainability, various measures have been implemented to reduce these harmful CO2 emissions. One of the solution is through Carbon capture storage (CCS) where carbon dioxide are captured and stored. With good abilities as an adsorbent in adsorption, the storage capabilities of Metal Organic Framework (MOFs) are investigated in details. Therefore, the objectives of this report aim to investigate the porous characteristics of the different adsorbents and determine if the various doped MIL-101(Cr) are able to surpass the adsorption uptake of the pure MIL-101(Cr) sample. In this report, six MOFs namely, Pure MIL-101(Cr), 1% K doped MIL-101(Cr), SiO2 doped MIL-101(Cr), Activated Carbon doped MIL-101(Cr), and 1% Li doped MIL 101(Cr) and 1% Na doped MIL-101(Cr) from previous raw data given, were studied with experimental temperature ranging from 220 K to 300 K, and pressures limited to 10 bar using the cryogenic and volumetric setup. The adsorbents were also analysed with SEM, XRD and BET to investigate on the modifications in structure, surface properties and surface areas.